Legal and Regulatory Framework of Nuclear Security in Indonesia - Dahlia Cakrawati Sinaga (International Journal of Nuclear Security, 2016)
Nuclear security is one of the most important topics for regulatory purposes in Indonesia. Nuclear security measures exist to prevent, detect, and respond to unauthorized removal of radioactive material and the sabotage of nuclear and radiation facilities. Indonesia participates in bilateral and multilateral cooperation and international events such as the Nuclear Security Summit. Indonesia has also ratified several international instruments related to nuclear security. Based on commitment to international events and ratification, Indonesia has developed nuclear security infrastructures by strengthening legislation and regulation, enhancing building capacity, and strengthening equipment and facilities. Badan Pengawas Tenaga Nuklir (BAPETEN) is Indonesia’s nuclear energy regulatory agency. Indonesia has issued regulatory acts related to nuclear security as a basis for BAPETEN’s regulatory activities. Indonesia has also issued several government regulations and BAPETEN Chairman Regulations addressing nuclear security. Indonesia is still developing legal and regulatory infrastructures by strengthening international cooperation and coordination with other stakeholders.